The Football Players' Health Study at Harvard University: Design and objectives. Issue 8 (18th June 2019) - Zafonte, Ross; Pascual‐Leone, Alvaro; Baggish, Aaron; Weisskopf, Marc G.; Taylor, Herman A.; Connor, Ann; Baker, Jillian; Cohan, Sarah; Valdivia, Chelsea; Courtney, Theodore K.; Cohen, I. Glenn; Speizer, Frank E.; et al.
Abstract: The Football Players Health Study at Harvard University (FPHS) is a unique transdisciplinary, strategic initiative addressing the challenges of former players' health after having participated in American style football (ASF). The whole player focused FPHS is designed to deepen understanding of the benefits and risks of participation in ASF, identify risks that are potentially reversible or preventable, and develop interventions or approaches to improve the health and wellbeing of former players. We are recruiting and following a cohort of former professional ASF players who played since 1960 (current n  = 3785). At baseline, participants complete a self‐administered standardized questionnaire, including initial reporting of exposure history and physician‐diagnosed health conditions. Additional arms of the initiative are addressing targeted studies, including promising primary, secondary, and tertiary interventions; extensive in‐person clinical phenotyping, and legal and ethical concerns of the play. This paper describes the components of the FPHS studies undertaken and completed thus far, as well as those studies currently underway or planned for the near future. We present our initiatives herein as a potential paradigm of one way to proceed (acknowledging that it is not the only way). We share what we have learned so that it may be useful to others, particularly in regard to trying to make professional sports meet the needs of multiple stakeholders ranging from players to owners, to fans, and possibly even to parents making decisions for their children.